Customer satisfaction : a SERVQUAL study on QB House hair salons. - Seet, Karen. (2008)
The purpose of this research is to explore the differences between consumer expectations of the QB House concept and their perceptions of the actual service. It attempts to identify and give explanations to the areas in which customers expectations have not been met. At the same time, it aims to better understand the customer base and provide current insights into QB House’s novelty haircut concept.